Effectiveness of Fungus Aspergillus sp. and Endofit Fungus as Bioremediation for Batik Pewarna Waste in Lake Teluk - Ulhaq, Mi'Rajul Auliya; Novrianti, Harum Salsabila; Yerdi, Nisyaroza; Sihombing, Marsaulina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Batik wastewater contains toxic pollutants such as chromium (Cr) and lead (Pb), which cause serious environmental pollution, therefore eco-friendly remediation methods are required. This study aimed to evaluate the effectiveness of Aspergillus sp. and endophytic fungi as bioremediation agents in reducing the color intensity of batik dye wastewater from Lake Teluk, Jambi. The research was conducted through an experimental design using two pre-incubation treatments, namely 24 hours and 5 days, before fungi were applied to the wastewater. The effectiveness of the treatment was measured using a UV-Vis spectrophotometer at 550 nm, and the percentage of decolorization was analyzed by comparing results across treatments. The results showed that Aspergillus sp. with a 5-day pre-incubation achieved the highest color reduction of 40.87%, whereas the 24-hour pre-incubation of both Aspergillus sp. and endophytic fungi only reduced color intensity by about 27–29%. These findings demonstrate that longer incubation time promotes mycelial growth and enhances enzymatic activity, including laccase and peroxidase, which accelerate dye degradation. It can be concluded that Aspergillus sp. is a more effective bioremediation agent than endophytic fungi, particularly with a 5-day pre-incubation period. The implication of this study suggests that further field-scale applications should be developed to establish Aspergillus sp. as a sustainable, safe, and efficient technology for batik wastewater management.